Relationship between the neutrophil-to-lymphocyte ratio in acute pancreatitis and the severity and systemic complications of the disease - Kokulu, Kamil; Günaydın, Yahya Kemal; Akıllı, Nazire Belgin; Köylü, Ramazan; Sert, Ekrem Taha; Köylü, Öznur; Cander, Başar (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: In 80% of the patients, Acute pancreatitis (AP) occurs as a self-limiting disease that does not require any specific treatment; however, in 20% of the cases it occurs in its clinically severe form that may lead to local or systemic complications. The aim of this prospective study was to examine the relationship between the neutrophil to lymphocyte ratio (NLR) and the systemic complications and severity of AP. Materials and Methods: This prospective study included 100 patients with AP. Age, sex, NLR, Ranson scores and the revised Atlanta classification of the patients were recorded. The patients were divided into two groups according to the Ranson scores as mild and severe AP. According to the Revised Atlanta classification, the patients were divided into two groups as mild and moderate+severe AP. Results: According to the Ranson score, NLR at the time of admission and at the 48th hour in the severe group was found to be statistically higher than the mild AP group (p7.13. Conclusion: Neutrophil to lymphocyte ratio is associated with severe AP. We also regard NLR as a valuable parameter for predicting the development of systemic complications in patients with AP. Cite this article as: Kokulu K, Günaydın YK, Akıllı NB, et al. The Relationship between the neutrophil-to-lymphocyte ratio in acute pancreatitis and the severity and systemic complications of the disease. Turk J Gastroenterol 2018; 29: 684-91.